Bioethical reflection regarding access to supplemental health in Brazil - Del Sarto Azevedo, Bruno; Santana Biondo, Chrisne; Lago da Silva Sena, Edite; Silva de Oliveira Boery, Rita Narriman; Donha Yarid, Sérgio (Acta Bioethica, 2015)
It is an integrative review that aims to develop a bioethical reflection based on what the scientific literature has been researching about the Brazilian population’s access to supplemental health. A search was conducted in the Virtual Health Library, using descriptors, from Health Sciences Descriptors, related to the studied theme, resulting in the selection of seven articles. It was evidenced that access to supplemental health services is fully achieved only by specific groups of people, which is symptomatic of a certain malaise that plagues the Brazilian society, due to the subpar conditions of the public sector and the elitism of the particular services. This fact leads to the consequent transgression of bioethical principles such as equality, justice and equity. As such, it becomes apparent that bioethical reflections on discussions about the respect for individual autonomy, with full right to seek access to private insurances as a means of seeing one’s health problems solved, and on the responsibility of the State as the implementation of an equitable access to health care and quality service to citizens, must be incorporated.